The Role of Fatty Acid Signaling in Islet Beta-Cell Adaptation to Normal Pregnancy - Kim, Jee-Hye; Delghingaro-Augusto, Viviane; Chan, Jeng Yie; Laybutt, D. Ross; Proietto, Joseph; Nolan, Christopher J. (Frontiers in Endocrinology, 2022)
Background: Maintenance of a normal fetal nutrient supply requires major adaptations in maternal metabolic physiology, including of the islet beta-cell. The role of lipid signaling processes in the mechanisms of islet beta-cell adaptation to pregnancy has been minimally investigated. Objective: To determine the effects of pregnancy on islet fatty acid (FA) metabolic partitioning and FA augmentation of glucose-stimulated insulin secretion (GSIS). Methods: Age matched virgin, early pregnant (gestational day-11, G11) and late pregnant (G19) Sprague-Dawley rats were studied. Fasted and fed state biochemistry, oral glucose tolerance tests (OGTT), and fasted and post-OGTT liver glycogen, were determined to assess in vivo metabolic characteristics. In isolated islets, FA (BSA-bound palmitate 0.25 mmol/l) augmentation of GSIS, FA partitioning into esterification and oxidation processes using metabolic tracer techniques, lipolysis by glycerol release, triglycerides (TG) content, and the expression of key beta-cell genes were determined. Results: Plasma glucose in pregnancy was lower, including during the OGTT (glucose area under the curve 0-120 min (AUC0-120); 655+/-24 versus 849+/-13 mmol.l-1.min; G19 vs virgin; P<0.0001), with plasma insulin concentrations equivalent to those of virgin rats (insulin AUC0-120; 97+/-7 versus 83+/-7 ng.ml-1.min; G19 vs virgin; not significant). Liver glycogen was depleted in fasted G19 rats with full recovery after oral glucose. Serum TG increased during pregnancy (4.4+/-0.4, 6.7+/-0.5; 17.1+/-1.5 mmol/l; virgin, G11, G19, P<0.0001), and islet TG content decreased (147+/-42, 172+/-27, 73+/-13 ng/µg protein; virgin, G11, G19; P<0.01). GSIS in isolated islets was increased in G19 compared to virgin rats, and this effect was augmented in the presence of FA. FA esterification into phospholipids, monoacylglycerols and TG were increased, whereas FA oxidation was reduced, in islets of pregnant compared to virgin rats, with variable effects on lipolysis dependent on gestational age. Expression of Ppargc1a, a key regulator of mitochondrial metabolism, was reduced by 51% in G11 and 64% in G19 pregnant rat islets compared to virgin rat islets (P<0.001). Conclusion: A lowered set-point for islet and hepatic glucose homeostasis in the pregnant rat has been confirmed. Islet adaptation to pregnancy includes increased FA esterification, reduced FA oxidation, and enhanced FA augmentation of glucose-stimulated insulin secretion.